Debt Management Performance Assessment Methodology : 2021 Edition - World Bank (World Bank, Washington, DC, 2021)
The Debt Management Performance Assessment (DeMPA) is the World Bank’s diagnostic tool for assessing performance using a comprehensive set of indicators that span the full range of government debt management (DM) functions. Launched in 2007, revised in 2015, the indicators have become an internationally recognized standard in the government DM field and can be applied in all developing countries. The DeMPA offers a sound diagnostic framework that allows a country’s DM processes and institutions to be evaluated against sound international practice, identifying core strengths and weaknesses, and thereby helping strengthen capacity and institutions so that countries can manage their government debt effectively and sustainably. It will assist countries that want to undertake debt management reforms, helping to monitor progress with achieving government DM objectives consistent with international sound practice. The DeMPA is modeled on the Public Expenditure and Financial Accountability (PEFA) indicators, however, it uses a more comprehensive set of indicators, spanning the full range of government debt management (DM) functions, to provide a detailed assessment of government DM. The DeMPA methodology consists of two parts: i) a description of the methodology and ii) an evaluation tool that summarizes key questions that should be assessed in the context of a DeMPA evaluation.